SLC6A3 Polymorphism Predisposes to Dopamine Overdose in Parkinson's Disease - Robertson, Brian D.; Al Jaja, Abdullah S.; MacDonald, Alex A.; Hiebert, Nole M.; Tamjeedi, Ruzbeh; Seergobin, Ken N.; Schwarz, Ute I.; Kim, Richard B.; MacDonald, Penny A. (Frontiers in Neurology, 2018)
In Parkinson’s disease (PD), cognitive functions mediated by brain regions innervated by the substantia nigra pars compacta (SNc) improve with dopamine replacement therapy, whereas, functions mediated by regions innervated by the ventral tegmental area (VTA) worsen. We investigated whether these effects are modulated by the presence of a common polymorphism (9R) in SLC6A3, the gene that encodes dopamine transporter (DAT). 9R carriers have higher DAT concentrations and subsequently lower baseline dopamine concentrations than wildtype individuals. We investigated the effect of SLC6A3 genotype on encoding and recall of abstract images using the Aggie Figures Learning Test in PD patients both on and off medication. Encoding depends upon brain regions innervated by the VTA, whereas recall depends upon brain regions innervated by the SNc. We found that dopaminergic therapy worsened encoding of abstract images in 9R carriers only. In contrast, dopaminergic therapy improved recall of abstract images in all PD patients, irrespective of SLC6A3 genotype. We found that 9R-carrier PD patients are predisposed to dopamine overdose and medication-induced impairment of cognitive functions mediated by VTA-innervated brain regions. Interestingly, PD patients without the 9R polymorphism did not show such an impairment. SLC6A3 genotype does not modulate the dopaminergic therapy-induced improvement of functions mediated by SNc-innervated regions in PD patients.